Development of integrated strategies using non-recombinant yeast for 2G ethanol production from lignocellulosic materials - Sandri, Juliana Passamani (Universidade Federal de São Carlos, 2023)
The viability of second-generation (2G) ethanol production still requires overcoming some bottlenecks, such as the underutilization of the hemicellulosic fraction of biomass and process improvements to reach higher productivity and economic viability. In this sense, the present project aimed to study and develop strategies for efficient 2G ethanol production, taking full advantage of biomass sugars and using non-recombinant yeasts and commercial enzymes, besides evaluating processes integration for first (1G) and 2G ethanol production. Simultaneous Isomerization and Fermentation (SIF) studies were carried out with commercial yeasts (S. cerevisiae Itaiquara and FT858L) and enzymes (xylose isomerases IGI-HF and Sweetzyme IT extra). Both enzymes were adequate to operate under SIF conditions (pH 5.2, 35 °C), whilst the baker’s yeast Itaiquara had better performance in fermenting xylulose. Mass transfer limitations in the SIF were circumvented by designing and operating the denominated “enzyme-multiple-packed bed reactor” (EMPBR), consisting of several tubes for enzyme load (53 IU/mL), which enabled its recycling in a process that resulted in ethanol productivities of about 0.87 getOH/L/h in xylose synthetic medium. The EMPBR was also applied for Simultaneous (Saccharification) Isomerization and Co-Fermentation (SICF/SSICF). The best strategy for hexoses and pentoses co-fermentation was evaluated in a defined medium mimicking industrial hydrolysate, with 12% of the total ethanol produced coming from xylose. Then, EMPBR performance was evaluated in industrial media, consisting of hemicellulosic hydrolysates mixed with pretreated solids (2G) or molasses (1G), supplemented with the commercial enzyme preparation Cellic®CTec2, under the concepts of 1G/2G process integration and whole sugarcane bagasse use. Hydrothermal hydrolysate fermented in a sequential strategy with molasses resulted in 76% of xylose conversion and 46 g/L of ethanol titer. Co-cultures with the yeasts K. marxianus and S. cerevisiae, aiming at improvements in the co-fermentation of hexoses and pentoses, were carried out in 24 deep-well plates, which allowed the screening of different culture conditions. A promising xylose conversion (83%) was achieved compared to monoculture (52%, K. marxianus), in hemicellulosic hydrolysate medium supplemented with nutrients (35 °C, 150 rpm, Vmedium: 2/5 of deep-well volume, CXi: 5 g/L). Further studies of the enzymatic hydrolysis process of the entire fraction of pretreated sugarcane bagasse were conducted on a small scale, reaching 37.5% cellulose conversion with 20% (w/v) of solids after 72 h at 35 °C. Scaleup of the process was carried out in a bioreactor designed for high solid load (HSL) processes. Solid feeding strategies were evaluated, achieving 64 and 75% cellulose conversion with 22.5% solids (w/v) after 72 h at 35 and 50 °C, respectively. Simultaneous Saccharification and Co-Fermentation (SSCF) with 15% solids were conducted with co-culture under the optimal conditions found in the 24-well plate study, resulting in 98% glucose and 52% xylose conversions, respectively, in 72 h, ethanol yield of 0.23 getOH/gS and productivity of 0.28 getOH/L/h. However, cell viability loss was observed during the HSL bioreactor operation, requiring modifications in the culture strategy. Overall, a great advance in the 2G processes using non-recombinant yeasts and commercial enzymes was achieved, as well as promising results for integrating the 1G/2G ethanol production processes.
Desenvolvimento de estratégias integradas utilizando leveduras não recombinantes para produção de etanol 2G a partir de materiais lignocelulósicos
Keywords: Bioethanol; Second generation processes; Biomass; Non-recombinant Yeasts; Commercial enzymes; Hemicellulose; Biorefinery; Bioetanol; Processos de segunda-geração; Biomassa; Leveduras não recombinantes; Enzimas comerciais; Hemicelulose; Biorrefinaria; ENGENHARIAS::ENGENHARIA QUIMICA